Partisipasi Masyarakat Tionghoa dalam Pelaksanaan Musrenbang Pada Kelurahan Sukadamai - Muhammad Adi Kurniawan; Badaruddin Badaruddin; Humaizi Humaizi (PERSPEKTIF, 2021)
The title of this research is Participation of Chinese Society in the Implementation of Musrenbang at Sukadamai Village. This research  aims to analyze the participation process of the Chinese ethnic community in the Musrenbang in Sukadamai Village, Medan Polonia District and tounderstand the forms of participation Chinese ethnic society in the Musrenbang in Sukadamai Village, Medan Polonia District. Theory in this research used theory of participation. The method used is qualitative data analysis. The data collection techniques are observation, interviews and literature study. The Musrenbang process of Sukadamai Village, Medan Polonia District consists of Pre-preparation, Implementation and Closing and in each of these stages, the Chinese ethnic society is actively involved. Forms of community participation, the Chinese ethnic in the Musrenbang of Sukadamai Village, Medan Polonia District include; thoughts, energy, expertise, goods and money.